2021
DOI: 10.1152/ajpgi.00188.2021
|View full text |Cite
|
Sign up to set email alerts
|

Cellular origins and lineage relationships of the intestinal epithelium

Abstract: Knowledge of the development and hierarchical organization of tissues is key to understanding how they are perturbed in injury and disease, as well as how they may be therapeutically manipulated to restore homeostasis. The rapidly regenerating intestinal epithelium harbors diverse cell types and their lineage relationships have been studied using numerous approaches, from classical label-retaining and genetic lineage tracing methods to novel transcriptome-based annotations. Here, we describe the developmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 130 publications
1
11
0
Order By: Relevance
“…In a recent technical tour de force, Cagan and colleagues have found that the rate of somatic mutation, as measured in the intestine, scales with age. 23 This effect, no doubt protective of cancer, is unlikely to be the result of the decline in the Mitotic Fraction , as the cells in the intestine undergo a rate of mitosis vastly greater than the Mitotic Fraction in the body as a whole (although one point of view holds that the precursors of the crypt stem cells may have a more conventional level of mitotic activity 53,54 ). As the authors concluded, “The most notable finding of this study is the inverse scaling of somatic mutation rates with lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent technical tour de force, Cagan and colleagues have found that the rate of somatic mutation, as measured in the intestine, scales with age. 23 This effect, no doubt protective of cancer, is unlikely to be the result of the decline in the Mitotic Fraction , as the cells in the intestine undergo a rate of mitosis vastly greater than the Mitotic Fraction in the body as a whole (although one point of view holds that the precursors of the crypt stem cells may have a more conventional level of mitotic activity 53,54 ). As the authors concluded, “The most notable finding of this study is the inverse scaling of somatic mutation rates with lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…It also has some of the same problems as phenetics. Breaking up continuous variation can involve subjective decisions (e.g., Cembrowski and Menon, 2018 ; Sagar and Grün, 2020 ), and the identification of biologically meaningful clusters from the high dimensional data produced by expression of 20,000 or more genes ( Efroni, 2018 ; Quake, 2021 ) makes clustering more an art than a science ( Kobak and Berens, 2019 ; Capdevila et al, 2021 ). Indeed, Chari et al (2021) referred to single cell genomics as a “specious art” based on their finding that commonly used unsupervised clustering approaches for dimensionality reduction do a poor job of grouping adjacent cells in this complex parameter space.…”
Section: Phenetics and Cladisticsmentioning
confidence: 99%
“…Some cells in the intestine can sense chemical and mechanical stimuli. Previous studies have classified the intestinal epithelium components as intestinal stem cells, enterocytes, goblet cells, tuft cells, enteroendocrine cells (EECs), and Paneth cells [ 7 ]. Epithelial cells work together to create a semipermeable barrier and are responsible for digestion, absorption, and immunity [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%